Zombies. Issue 5 (December 2014) - Zelterman, Daniel
<x xml:space="preserve">Abstract</x> What if zombies were real? And what if, rather than wiping out humanity, we found a way to coexist, to manage the problem? We would need data, of course information about the undead horde – to help develop an appropriate civil response. And we would need people like Daniel Zelterman, professor of biostatistics at Yale University, to compile and analyse that data. In this extract from the new book, Mathematical Modelling of Zombies – billed as a maths‐based survival guide – Zelterman explores the distribution of the US zombie population in the days, weeks and months that followed the night of the living dead